The analysis of density and types of mangroves on the coast of Aceh Tamiang district - Maharani Maharani; Muhammad Irham; Muhammad Rusdi (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2025)
Mangrove plants have the capacity to protect coastlines and inland areas from natural disasters such as hurricanes, cyclones, and tsunamis. Mangroves are one of the most productive marine ecosystems on earth, providing unique habitat for many species, as well as important goods and services for humans. Mangroves are also a spawning ground and nursery ground for various types of marine biota. The mangrove area in the Aceh Tamiang area is currently in trouble because of the many activities such as changing the function of land as ponds, housing, infrastructure development and making charcoal kitchens, which can change the function of the mangroves. For this reason, it is necessary to carry out research with the aim of mapping the distribution of mangrove ecosystems using multi-temporal satellite imagery, classifying mangroves based on their density classes and finding out the type of mangrove that is dominant in the mangrove density. This research uses the Purposive Random Sampling method as a technique for taking several scientific considerations. This research also uses the NDVI (Normalized Difference Vegetation Index) method by categorizing 3 classes in density in the Seruway, Bendahara, Banda Mulia and Manyak Payed Subdistricts in five different periods, namely 2002, 2007, 2012, 2017 and 2022. The results obtained the highest NDVI value was in 2002 at 0.98 with an area of 2152.61 ha (16.52%) and the lowest value was in 2007 at -0.23 with an area of 474.15 ha (4.47%). The total type of mangrove found in Aceh Tamiang District is 27 types. Seruway Subdistrict found the most types of mangroves, around 23 types, and in Banda Mulia Subdistrict, the fewest types of mangroves were found, around 12 types.Keywords:Mangrove ecosystemNDVI methodMangrove densityCoastal LULCMangrove type